2020
DOI: 10.1097/rlu.0000000000003229
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Schwannoma on FDG PET/CT

Abstract: A 55-year-old woman underwent FDG PET/CT to evaluate a pancreatic mass. The images showed elevated FDG activity in the uncinated process of the pancreas, suggestive of malignancy. However, pathological examination from the resected lesion demonstrated pancreatic schwannoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…To date, all 5 cases of pancreatic schwannoma that underwent PET/CT had increased FDG uptake. [8,17,23,29] Recently, an increasing number of cases have undergone endoscopic ultrasound fine needle aspiration (EUS-FNA), which has greatly contributed to precise preoperative diagnosis. Of the 12 patients with pancreatic schwannoma who underwent EUS-FNA, 9 were accurately diagnosed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, all 5 cases of pancreatic schwannoma that underwent PET/CT had increased FDG uptake. [8,17,23,29] Recently, an increasing number of cases have undergone endoscopic ultrasound fine needle aspiration (EUS-FNA), which has greatly contributed to precise preoperative diagnosis. Of the 12 patients with pancreatic schwannoma who underwent EUS-FNA, 9 were accurately diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…On 18F-fluorodeoxyglucose positron emission tomography (FDG-PET), elevated FDG activity in schwannomas has been reported, [90] even though they are usually benign. To date, all 5 cases of pancreatic schwannoma that underwent PET/CT had increased FDG uptake [8,17,23,29] . Recently, an increasing number of cases have undergone endoscopic ultrasound fine needle aspiration (EUS-FNA), which has greatly contributed to precise preoperative diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to other pancreatic tumors. Imaging modalities, including CT, MRI, and endoscopic ultrasound, can help to identify the pancreatic mass but cannot distinguish pancreatic schwannoma from other tumor types of the pancreas because of its wide range of morphologies [4]. Pancreatic schwannoma might appear as a solid, cystic, or as compound lesion [2,[5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…When pancreatic schwannoma appears as a mixed lesion of solid and cystic components, it resembles malignant pancreatic tumors and can be perceived that way even though pancreatic schwannoma is benign in the majority of cases. Some studies have shown that pancreatic schwannomas are also highly metabolic and light up on positron emission tomography-computed tomography scans, which also might be mistaken for malignancy [4,9]. This similarity might pose a risk for possible misdiagnosis and inappropriate management in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] The false-positive 18 F-FDG uptake in the schwannomas, especially in those with unexpected location, are easily lead to the misinterpretation of schwannomas as malignancy in the imaging diagnosis. [11][12][13][14][15] PS arising from the pelvis is an extremely rare subtype of schwannoma, thus the literature on its 18 F-FDG PET/MRI findings was limited. For this reason, we report the findings on 18 F-FDG PET/MRI of this rare case of pelvic PS to provide further insight into diagnosing this kind of rare tumor.…”
Section: Figurementioning
confidence: 99%